Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

A + B + C = π (cotA+cotB+cotC)÷(cotA×cotB×cotC) = (a) 1 (b) cotAcotBcotC (c) -1 (d) 0 My attempt at solution: Let A = B = C = π÷3 Then, cot(A) + cot(B) + cot(C) = 3 × cot(π÷6) = 3 × (1÷√3) = √3 And, cotA × cotB × cotC = (1÷√3)^(3) =1÷(3√3) Therefore, answer should be 9. What am I doing wrong? Source: BITSAT Paper 2012.

A + B + C = π
 
(cotA+cotB+cotC)÷(cotA×cotB×cotC) =  
 
(a) 1
(b) cotAcotBcotC
(c) -1
(d) 0
 
My attempt at solution:
 
Let A = B = C = π÷3
 
Then,
cot(A) + cot(B) + cot(C) = 3 × cot(π÷6) = 3 × (1÷√3) = √3
 
And,
cotA × cotB × cotC = (1÷√3)^(3) =1÷(3√3)
 
Therefore, answer should be 9.
What am I doing wrong?
Source: BITSAT Paper 2012.
 
 
 

Grade:12th pass

1 Answers

Saurabh Koranglekar
askIITians Faculty 10341 Points
2 years ago
Dear student

The correct answer is not mentioned

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free